Economic optimization of hybrid renewable energy systems supplying electrical and thermal loads of a tourist building in different climates - Hajinejad, Ahmad; Seraj, Farhad; Jahangir, Mohammad Hossein; Askari, Minoo (Frontiers in Built Environment, 2023)
Due to the high potential of tourism in Iran and the high utilization of tourist buildings in Iran, as well as the high energy consumption in the buildings sector, this study aims to provide a feasible model for designing a renewable energy supply system for a tourist building in different climates of Iran. According to the country’s climate, 5 cities of Ahvaz, Bandar Abbas, Rasht, Mashhad, and Yazd were selected as the cities under study. The hybrid system also consists of photovoltaic panels, wind turbine, battery, and converter for power supply and boilers with natural gas fuel and geothermal heat pump to provide building thermal load. The heat pump is used to supply the load needed to preheat the building’s hot water. The system is connected to the electricity grid, so by selling excess electricity, the net project costs (NPC) will be reduced and the system can provide part of its need from the grid. The scenarios which were studied are of two categories. In the first category, all the thermal load is supplied by the boiler. After selecting the best economic scenario by Homer software in this category, the heat pump is added to the system by calculating the thermal load required to preheat the hot water. The scenarios used two types of wind turbines with a capacity of 10 and 50 kW and two types of 25-W panels with different efficiencies of 15.3% and 18%. Finally, a top-down scenario was chosen for each city. The best city to run the project on economic criteria is Mashhad with an NPC of $ 195,745 and a renewable fraction of $ 50.5. Using a heat pump to preheat the hot water, would also save 7% on fuel consumption and reduce CO2 production by 639,000 kg per year.